Optimized Detection of Acute MHV68 Infection With a Reporter System Identifies Large Peritoneal Macrophages as a Dominant Target of Primary Infection - Riggs, Julianne B.; Medina, Eva M.; Perrenoud, Loni J.; Bonilla, Diana L.; Clambey, Eric T.; van Dyk, Linda F.; Berg, Leslie J. (Frontiers in Microbiology, 2021)
Investigating the dynamics of virus-host interactions in vivo remains an important challenge, often limited by the ability to directly identify virally-infected cells. Here, we utilize a beta-lactamase activated fluorescent substrate to identify primary targets of murine gammaherpesvirus 68 (MHV68) infection in the peritoneal cavity. By optimizing substrate and detection conditions, we were able to achieve multiparameter characterization of infected cells and the ensuing host response. MHV68 infection leads to a pronounced increase in immune cells, with CD8+ T cells increasing by 3 days, and total infiltrate peaking around 8 days post-infection. MHV68 infection results in near elimination of large peritoneal macrophages by 8 days post-infection, and a concordant increase in small peritoneal macrophages and monocytes. Infection is associated with prolonged changes to myeloid cells, with a distinct population of MHC IIhigh large peritoneal macrophages emerging by 14 days. Targets of MHV68 infection could be readily detected. Between 1 to 3 days post-infection, MHV68 infects ~5-10% of peritoneal cells, with >75% being large peritoneal macrophages. By 8 days post-infection, the frequency of MHV68 infection is reduced at least 10-fold, with infection primarily in small peritoneal macrophages, with few infected dendritic cells and B cells. Importantly, limiting dilution analysis indicates that at 3 days post-infection, the majority of MHV68-infected cells harbor latent rather than lytic virus at frequencies consistent with those identified based on reporter gene expression. Our findings demonstrate the utility of the beta-lactamase MHV68 reporter system for high throughput single-cell analysis and identify dynamic changes during primary gammaherpesvirus infection.